The effect of a convection vortex on sock formation in the floating catalyst method for carbon nanotube synthesis. (June 2016) - Hou, Guangfeng; Su, Ruitao; Wang, Anli; Ng, Vianessa; Li, Weifeng; Song, Yi; Zhang, Lu; Sundaram, Murali; Shanov, Vesselin; Mast, David; Lashmore, David; Schulz, Mark; et al.
Abstract: The formation of an aerogel-like sock is important to the floating catalyst method of synthesizing carbon nanotubes (CNTs). The sock, a term coined by Alan Windle, is an assembly of the individual electrostatically assembled nanotubes synthesized in the reactor. The coherency of this sock helps form the yarn or sheet. In this study, sock formation is investigated by controlling the feedstock type, injection rate, and carrier gas flow rate. A convection vortex has been identified, possibly for the first time, in the floating catalyst method. A convection vortex model is proposed to explain the sock formation. The sock morphology is found to be strongly affected by the carrier gas flowrate, where too high gas flowrate reduces the concentration of CNTs in the reactor resulting a failure in the sock formation. The dynamic behavior of the sock is explained by a web-shell structure.